Effect of using titanium interlayers on the properties of vitrified diamond tools. (2nd December 2009) - Jackson, Mark J.; Xiao-fu, Zhang
In this paper, diamond crystals are coated with titanium films in order to improve the chemical properties of diamond. The impact strength, oxidisation characteristics and the effects of sintering temperature on vitrified bond and diamond are investigated. It is found that when a titanium film is coated on the surface of diamond the contact angle between vitrified bond and diamond decreased from 39.5% to 34.5% at 993 K and that the degree of oxidisation on the surface of diamond will significantly decrease.